Testing For Trade Gravity Model Between Syria And Iraq Using Least Squares With Breakpoints Method During The Period (2002-2019) - إياد زيتي; فادي خليل (Latakia University Journal - Economic and Legal Sciences Series, 2022)
This research aims to test the application of the gravity model proposed by Jan Tinbergen (1963) on intra-trade between Syria and Iraq. To do so, database over the period 2002-2019 is used depending on the data published by CBS and Unctad. The intra-trade size is measured by the total exports and imports registered between both countries, and then the mass in the gravity model is estimated by using the natural logarithm of the product of GDPs in both countries. Given the common geographical borders, the economic distance represented by the difference between the two countries’ GDP per capita is used instead. The gravity model is estimated by implementing Breakpoints least squares estimator (LSBP) which is helpful to take in account the specificity of the study period with the expected presence of structural breaks points. The LSBP method produces good residuals characters (normally distributed, no serial correlation, homogeneity of variance). Besides, it seems that the intra-trade between Syria and Iraq is subject to the gravity model. Indeed, this trade is related positively with the mass of the two countries’ GDPs, and negatively with the economic distance.